Charitable Contributions: New Evidence on Household Behavior - Reece, William S. (American Economic Review, 1979)
In this paper I provide some new empirical evidence on the impact of tax deductibility on the level of personal charitable contributions. In order to provide empirical evidence of this kind we have to consider the broader question of the determination of the level of charitable giving by the household. The price of which is dependent upon the tax treatment of those contributions, is only one element of this process. Efforts to quantify the impact of tax deductibility lead to an empirical model which allows us to test a number of hypotheses on the determination of the level of charitable contributions. In Section I, a model of personal charitable giving and its empirical implications are discussed. In Section 1I previous attempts to test some of these implications and to quantify the impact of tax deductibility on charitable giving are discussed. Section III presents the specification of the empirical model including a discussion of the data, and Section IV presents empirical results. In Section V the implications of these results are summarized.